SISTEM MANAJEMEN MUTU TERPADU DALAM UPAYA MENINGKATKAN KUALITAS PRODUK PADA PERUSAHAAN - Simbolon, Sahat (UNIKA Santo Thomas, 2014)
One of the strategies to be used in order to defeat competitors in this globalization era is to implement total quality management.Companies that implement total quality management will product and market more qualified products.Total quality management intends to evaluate in all work fields with customer satisfaction orientation.total quality managementhas become important in several organization aspects, such as: Accounting, Finance, Human Resource, Management Information System, Marketing, and Operation. This method is done by collecting product data produced.Organization implements total quality management by doing development individually and develop managerial employees professionalism, forming group work, measuring the managerial effectiveness, increasing work productivity, implement continuous correction, employees empowerment and just in time. The company earned profit will result in profitability and growth of the company.